Proposals for Second Five Year Plan Panchayat Sector Government of Rajasthan - Planning Commission (Planning Commission, 1955)
Panchayat Extension-Officers have already been provided under the Community Development set up. Over and above this, Rs. I0 lakhs are proposed to be spent on the training camps to be organized for Panchayat Officers and Panchayat and for partial assistance for the construction and development of Panchayat Ghars, as ferreters of Tribal activities in the rural areas.
Government of Rajasthan
Panchayat Sector
Keywords: Introduction Panchayats; Training Centers for Assistant; Inspectors and Panchayat Office bearers; Subsidy for the construction; Subsidy for village recreation equipments; Expenditure in connection with Sarpanchas Training; Budget Estimates for two Training Centre; Establishment; Lower Division; Furniture and other Office equipment